EVALUASI KINERJA PROGRAM STUDI EKONOMI SYARIAH FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN SAMARINDA PASCA AKREDITASI - Yusran Yusran; Rachmad Saleh Nasution (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2020)
This study aims to determine the perception of the IAIN lecturer at the Faculty of Economics and Islamic Business. This research method uses qualitative methods with data collection techniques such as questionnaires and data analysis using descriptive analysis. This study found that the 6 performance standards set by BANT PT, namely standard 1 about vision and mission, goals and objectives and achievement strategies, standard 2 governance, leadership, management and quality assurance systems, standard 4 human resources, and standard 5 learning curriculum and academic atmosphere, standard 6 for financing facilities and infrastructure as well as information systems, and standard 7 related to research, service and community service and collaboration in general are felt by lecturers in the satisfied or good category.